Physician‐performed chest ultrasound: progress and future directions. Issue 3 (March 2017) - Denton, Eve J.; Hannan, Liam M.; Hew, Mark
Abstract : Background: Pleural ultrasound guidance reduces complications of pleural procedures, and lung ultrasound can diagnose the cause of acute respiratory failure. Yet as recently as 5 years ago, many respiratory physicians lacked sufficient access, training and expertise to perform a chest ultrasound. Aims: This study examines whether progress has been achieved in chest ultrasound amongst respiratory physicians in Australia and New Zealand. Methods: We conducted a web‐based chest ultrasound survey of adult respiratory physicians across Australia and New Zealand. We also surveyed advanced trainees. Results: The response rate was 38% among respiratory physicians. Between 2011 and 2016, access to bedside ultrasound increased from 53 to 90%. The proportion arranging ultrasound guidance for pleural aspiration rose from 66 to 95%. The proportion demonstrably competent in pleural ultrasound increased from 4 to 21%. In 2016, 67% of physicians and 80% of advanced trainees reported available workplace supervision for ultrasound training. Use of lung ultrasound to diagnose acute pulmonary oedema and consolidation improved from 2011 but remained low at 25 and 20% respectively. Conclusion: These results establish pleural ultrasound guidance for pleural procedures as the standard of care in our region. However, lung ultrasound remains underutilised. Ultrasound training can and should be incorporated into specialist respiratory training.